The Ca2+ Sensor Calcineurin B–Like Protein 10 in Plants: Emerging New Crucial Roles for Plant Abiotic Stress Tolerance - Plasencia, Felix A.; Estrada, Yanira; Flores, Francisco B.; Ortíz-Atienza, Ana; Lozano, Rafael; Egea, Isabel (Frontiers in Plant Science, 2021)
Ca2+ is a second messenger that mediates plant responses to abiotic stress, and the Ca2+ signals need to be decoded by Ca2+ sensors that translate the signal into physiological, metabolic and molecular responses. Research on the Ca2+ sensor CALCINEURIN B-LIKE PROTEIN 10 (CBL10) in last years has resulted in important advances in the knowledge of the function of this signaling component in abiotic stress tolerance. Under salt stress, CBL10 function was initially related with regulation of Na+ homeostasis, protecting plant shoot from salt stress, where CBL10 interacts with the CBL-interacting protein kinase CIPK24 (SOS2), being this interaction localized both at plasma and vacuolar (tonoplast) membranes. Interestingly, recent studies revealed that CBL10 is a regulator not only of Na+ homeostasis but also of Ca2+ under salt stress, regulating Ca2+ fluxes in the vacuole, but also at the plasma membrane. This review summarizes the advances on CBL10 role in plant stress tolerance, mainly salt stress as this is the abiotic stress more studied until now in relation with the function of this regulator, with special focus on some aspects not clarified yet. We also focus on the proven versatility of CBL10 to activate (in a CIPK-dependent manner) or repress (by direct interaction) downstream targets, in different subcellular localizations, which in turn seems to be the reason by which CBL10 could be considered not only key master regulator of stress signaling in plants but also a crucial participant in fruit development and quality, as disruption of CBL10 revealed an inadequate Ca2+ partitioning in plant and fruit. New emerging roles in other abiotic stresses aside from salt stress, such as drought, flooding and K+ deficiency, will also be addressed in this review. Finally, we provide an overview on recent advances in potential targets of CBL10, as CBL10/CIPKs complexes and as CBL10 direct interactions. The aim is to show advances in the knowledge on this master regulator of abiotic stress tolerance that may be essential to maintain crop productivity under abiotic stress conditions, especially considering the scenario of a projected increasing extremes environmental conditions due to climate change.